The dynamic thermal performance of construction materials for satisfactory thermal comfort in the design of a terrace house in the Klang Valley, Malaysia / Mohammed Ali Abdul Hussain Al Obaidi - Mohammed Ali, Abdul Hussain Al Obaidi (2004)
The design of residential buildings has a significant impact on the people's daily life. The "terrace house" form constitutes the majority of the residential building stock in Malaysia. The lack of thermal comfort in terrace houses, reported so far, is mainly due to the poor thermal properties of the building materials, and design factors. This research aims at studying the dynamic factors of (i) temperature variations (hourly) and (ii) thermal comfort in spaces of the terrace housing in Malaysia. The main objective of the research is to study the effect of design and construction variations, space usage patterns and climatic conditions, so as to develop suitable models that incorporate these variables. The research can then report on the respective importance of design and construction variations, in the context of particular activity pattern and climatic conditions. This will be valuable to designers in evaluating the thermal comfort significance of design and construction decisions. The research variables have been divided into two types; (i) architectural design and (ii) constructional materials. The choice (ii) depends on their common use in the Malaysian terrace houses as well as to test the wide range of effects they have on the indoor air temperature. Meanwhile, the choice of (i) is related to the literature review of the Design Strategies and Design Principles in architecture. The climatic parameters in Malaysia (KL) are analysed over a thirty-year weather data period in order to find the typical "Design Day". This data is vital to the calculation. The climate in Malaysia can generally be described as tolerable in terms of thermal requirements. The common prototype design has been chosen in this study to represent the terrace house in Malaysia. A series of computer simulations using commercially available software known as the BLAST is conducted to evaluating the thermal comfort of design and the effect ofconstruction design decisions. The "BLAST" software was choosen because of the nature of the research objectives, aims, problems and the high number of variable used in this study. Moreover, it is a suitable and flexible tool to calculate dynamic temperature and thermal comfort. Regression techniques and correlations are chosen for statistical analysis to study the effects of various parameters (variables) on spaces and materials performance. Two famous software packages in statistical analysis, Microsoft SPSS v10.05 and Excel, have been chosen for this purpose. The study and simulation guidance is divided into three stages: (i) The first stage; concentrates on the analysis of the conditions in the existing case of the typical terrace house in Malaysia, by finding the dynamic indoor air temperature and the dynamic thermal comfort. (ii) The second stage; concentrates on exploring the effect of construction and design variables on the indoor air temperature and develop new models terrace house design called (lightweight and heavyweight) thermal mass, by revising and choosing the best parameters from the design and construction variables. (iii) The third stage; explains the effect of mechanical ventilation, "the ceiling fan",on the indoor dynamic thermal comfort ,firstly, for the existing typical terrace house and secondly, for the new terrace house design proposals that have been chosen previously to meet the maximum thermal comfort by changing air velocity. Finally, the new findings can be summarized as follows: 1) The study proposes new more comfortable models of the terrace house design. The models for (light and heavy) thermal masses are done by revising and choosing the best parameters from the Design and Construction variables, both utilizing the minimum amount of energy 2) The study presents the conditions of all spaces in the existing terrace house as well as effects of design and construction variables, individually or both, on the indoor air temperature and the thermal comfort in the terrace house. 3) This study has focused on the analysis of the dynamic indoor air temperature and dynamic thermal comfort within 24 hours, which is a new addition to the studies of thermal comfort in terrace houses in Malaysia. 4) The study explains the effect of construction and design variables in reducing the indoor air temperature which is very important to the designer and researcher. 5) The study explains the effect of mechanical ventilation, ceiling fan on the indoor dynamic thermal comfort, firstly, for existing typical terrace house. Secondly, on the two new model (light and heavy) that obtained from this thesis. 6) This research provides a tool for evaluating the thermal comfort of design and the effects of construction design decisions, using the BLAST software. 7) This study suggests the idea of a typical "Design Day" for Malaysia. This data is vital for the calculation. The climate in Malaysia can generally be described as tolerable in terms of thermal requirements. 8) The common and typical prototype terrace house design has been analyzed in this study to represent the zoning relationship in the terrace houses in Malaysia.